VGLUT3 does not synergize GABA/glycine release during functional refinement of an inhibitory auditory circuit - Case, Daniel T.; Alamilla, Javier; Gillespie, Deda C. (Frontiers in Neural Circuits, 2014)
The vesicular glutamate transporter VGLUT3 is expressed at several locations not normally associated with glutamate release. Although the function of this protein remains generally elusive, when expressed in non-glutamatergic synaptic terminals, VGLUT3 can not only allow glutamate co-transmission but also synergize the action of non-glutamate vesicular transporters. Interestingly, in the immature glycinergic projection between the medial nucleus of the trapezoid body (MNTB) and the lateral superior olive (LSO) of auditory brainstem, the transient early expression of VGLUT3 is required for normal developmental refinement. It has however been unknown whether the primary function of VGLUT3 in development of these inhibitory synapses is to enable glutamate release or to promote loading of inhibitory neurotransmitter through vesicular synergy. Using tissue from young mice in which Vglut3 had been genetically deleted, we evaluated inhibitory neurotransmission in the MNTB-LSO pathway. Our results show, in contrast to what has been seen at adult synapses, that VGLUT3 expression has little or no effect on vesicular synergy at the immature glycinergic synapse of brainstem. This finding supports the model that the primary function of increased VGLUT3 expression in the immature auditory brainstem is to enable glutamate release in a developing inhibitory circuit.